Statistics in the social sciences : current methodological developments - Kolenikov, Stanislav; Steinley, Douglas; Thombs, Lori A. (Ebook Central Academic Complete Collection, 2010)
A one-of-a-kind compilation of modern statistical methods designed to support and advance research across the social sciences. Statistics in the Social Sciences: Current Methodological Developments presents new and exciting statistical methodologies to help advance research and data analysis across the many disciplines in the social sciences. Quantitative methods in various subfields, from psychology to economics, are under demand for constant development and refinement. This volume features invited overview papers, as well as original research presented at the Sixth Annual Winemiller Conferen.